Novel modified side‐by‐side balloon dilatation method for esophagogastric junction strictures: Single‐/double‐barrel techniques. Issue 3 (12th January 2022) - Toshimori, Akiko; Inoue, Haruhiro; Fujiyoshi, Mary Raina Angeli; Fujiyoshi, Yusuke; Nishikawa, Yohei; Tanabe, Mayo; Shimamura, Yuto; Ohwada, Kaori; Ono, Masashi; Ikeda, Haruo; Onimaru, Manabu
Abstract : Endoscopic balloon dilatation is an established treatment for benign gastrointestinal strictures. In order to dilatate safely, it is necessary to dilatate gradually and preferably under direct endoscopic visualization. However, it is currently difficult to achieve dilatation widths of 20–30 mm with commercial products and of over 30‐mm with endoscopic visualization. Therefore, a safe and innovative application technique is needed for patients who need these 20‐mm or greater dilatation widths. We have developed two methods that enable more than 20‐mm dilatation under direct visualization. (i) Single‐barrel method: an endoscopic balloon dilatation catheter was fixed with grasping forceps at the tip of the endoscope and carried into the stomach. The balloon catheter was released from the endoscope to create a retroflexed view. The endoscope and balloon were positioned adjacent to each other at the gastric cardia. The balloon was inflated gradually and the esophagogastric junction was dilatated under direct visualization. (ii) Double‐barrel method: the same procedure was repeated with two balloons. Theoretically, we achieved a dilatation of >30‐mm in diameter. These modified methods may be helpful for esophagogastric junction strictures, such as esophageal achalasia (serving as an initial endoscopic balloon dilatation prior to using a 30‐mm achalasia balloon), or for functional strictures after Nissen fundoplication. In conclusion, our simple, modified method enables safe and gradual dilatation under direct endoscopic visualization. Additionally, combination of the sizes of one or two balloons can achieve various widths of dilatation.